Intrahousehold inequality at different welfare levels: energy intake and energy expenditure data from the Philippines - Haddad, Lawrence James; Kanbur, Ravi; Bouis, Howarth E. (Wiley, 1995)
This paper investigates the relationship between intrahousehold inequality and levels of household welfare. Under certain conditions it is demonstrated — with both the unitary model of the household and with some collective models — that the relationship between household welfare and inequality within the household can have an inverted u‐shape. Using two sets of calorie adequacy data from a sample of 455 households in the Philippines, a spline analysis is used to test the hypothesis that inequality within the household first increases and then decreases as per capita household total expenditure increases. The two sets of calorie adequacy data are based on repeated 24‐ hour recalls of dietary intake, and on calorie requirements that are unadjusted and then adjusted for individual activity patterns. Results indicate that once activity patterns are accounted for, calorie intake shortfalls are borne fairly equally within the household at all per capita household total expenditure levels.